ChemInform Abstract: Lewis Acid Catalyzed Tandem Polycyclization of Internal Alkynols and Vinyl Azides. Issue 12 (March 2016) - Siyang, Hai Xiao; Ji, Xiao Yue; Wu, Xu Rui; Wu, Xin Yan; Liu, Pei Nian
Abstract: Various [2‐(arylethinyl)phenyl]methanols are reacting with 1‐(1‐azidovinyl)arenes and hetarenes to deliver polycyclic pyran‐based indeno[1, 2‐c]isochromene scaffolds in moderate to high yields.